2020
DOI: 10.3892/br.2020.1347
|View full text |Cite
|
Sign up to set email alerts
|

Intranasal injection of recombinant human erythropoietin improves cognitive and visual impairments in chronic cerebral ischemia rats

Abstract: The present study aimed to study the protective effect of intranasally delivered recombinant human erythropoietin (rhEPO) on cognitive and visual impairments in a permanent bilateral common carotid artery occlusion (2VO)-induced chronic cerebral ischemia (CCI) rat model. Male Sprague-Dawley rats (age, 6 months) with 2VO-induced CCI were treated with intranasal rhEPO (50 U/100 g) once per week for 8 weeks. A Morris water maze was used to evaluate the spatial learning and memory of the rats. Flash visual evoked … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…For example, we treated the same animal model with intranasal ST266, a progenitor cellproduced therapy containing numerous growth factors and cytokines, and found significant RGC neuroprotective as well as optic nerve anti-inflammatory effects with this complex therapy [6,16], further supporting the idea that combined anti-inflammatory and neuroprotective therapies may be useful to attenuate optic neuritis. Zhou et al also showed that intranasal erythropoietin improves both cognitive and visual function in a cerebral ischemia rodent model [17]. Few, if any, other groups have examined intranasal drug delivery for treating optic neuropathies; however, intranasal delivery has been shown to bypass the blood-brain barrier for targeting central nervous system disease [18,19], including studies showing the potential effects of intranasal RSV on Alzheimer's disease [20].…”
Section: Discussionmentioning
confidence: 99%
“…For example, we treated the same animal model with intranasal ST266, a progenitor cellproduced therapy containing numerous growth factors and cytokines, and found significant RGC neuroprotective as well as optic nerve anti-inflammatory effects with this complex therapy [6,16], further supporting the idea that combined anti-inflammatory and neuroprotective therapies may be useful to attenuate optic neuritis. Zhou et al also showed that intranasal erythropoietin improves both cognitive and visual function in a cerebral ischemia rodent model [17]. Few, if any, other groups have examined intranasal drug delivery for treating optic neuropathies; however, intranasal delivery has been shown to bypass the blood-brain barrier for targeting central nervous system disease [18,19], including studies showing the potential effects of intranasal RSV on Alzheimer's disease [20].…”
Section: Discussionmentioning
confidence: 99%
“…All groups received 100 ml tested formulation, with 2.0 mg ibuprofen or blank. A nasal installation volume of 100 ml was considered as an acceptable delivery volume in rats (Zhou et al, 2020). The dose was calculated according to the lowest oral bioavailability dose in adult humans of 400 mg/tablet (in t ' Veld et al, 2001).…”
Section: Methodsmentioning
confidence: 99%